European itineraries in the geography of Bulgarian literature: Sofia – Paris (Colloquia Comparativa Litterarum, 2025)
At the beginning of the 20th century, Paris was the home of art, the intellectual capital of Europe, and the scene of the art of living. Among the many foreign artists and writers, Bulgarians formed an important colony. For these young artists who landed in the French capital, it was synonymous with celebration and freedom. The attractiveness of Paris, its cosmopolitanism, and the special place the City of Light occupied in Bulgarian imagination played the role of a catalyst for their creative talent. Their wanderings served as a bridge between the East and the West of a Europe, which had always been both united and torn between its centres and peripheries. Fascinated, dazzled, hypnotised by the brilliance of Paris as well as by its decay, Bulgarian writers lived the quest for identity – literary, existential, human – whose meanderings have been examined in this article.
Keywords: Paris; myth; image; Bulgaria; place of writing; elsewhere and text